COVID-19 and the case for global development. (October 2020) - Oldekop, Johan A.; Horner, Rory; Hulme, David; Adhikari, Roshan; Agarwal, Bina; Alford, Matthew; Bakewell, Oliver; Banks, Nicola; Barrientos, Stephanie; Bastia, Tanja; Bebbington, Anthony J.; Das, Upasak; et al.
Abstract: COVID-19 accentuates the case for a global, rather than an international, development paradigm. The novel disease is a prime example of a development challenge for all countries, through the failure of public health as a global public good. The COVID-19 pandemic has highlighted the falsity of any assumption that the global North has all the expertise and solutions to tackle global challenges, and has further highlighted the need for multi-directional learning and transformation in all countries towards a more sustainable and equitable world. We illustrate our argument for a global development paradigm by examining the implications of the COVID-19 pandemic across four themes or 'vignettes': global value chains, digitalisation, debt, and climate change. We conclude that development studies must adapt to a very different context from when the field emerged in the mid-20th century.